Experiment on reducing lateral earth pressure with a biopolymer-treated layer and geogrid-reinforced sand backfill - Kim, Gi Yun; Lee, Hwijae; Chang, Ilhan (Smart Geotechnics for Smart Societies, 2023)
In general, the common active earth pressure theory used for retaining wall design has several limitations which render ineffective over estimation and conservative design. Recently, biopolymer-based soil treatment (BPST) is considered as a new ground improvement practice in terms of sufficient shear strength enhancement via hydrogel induced interparticle bonding. In this study, an experimental setup which allows wall rotation subjected to the bottom toe is used to monitor the lateral earth pressure variation with wall rotation. Different backfill conditions were considered to assess the BPST effect on the active lateral earth pressure behavior. Experimental results indicate that a dehydrated BPST layer embedded in the backfill reduces the active lateral earth pressure which is similar to the reinforcement effect of a geogrid layer installation.